The Distribution Characteristics and Human Health Risks of High- Fluorine Groundwater in Coastal Plain: A Case Study in Southern Laizhou Bay, China - Liu, Sen; Liu, Yanan; Wang, Cong; Dang, Xianzhang (Frontiers in Environmental Science, 2022)
High-F groundwater has caused serious human health problems worldwide. In this paper, a typical saline-fresh water mixing zone (SFMZ) in a coastal plain (south of Laizhou Bay, China) was chosen as an example to analyze and summarize the distribution characteristics and enrichment mechanism human health risks of high-fluorine groundwater. Thirty-two groundwater samples have F- concentrations that exceed the drinking water guideline value of the World Health Organization (WHO; 1.5 mg/L), Thirty-two groundwater samples exceeded the drinking water guideline value of the WHO (1.5 mg/L) and 43 groundwater samples exceeded the National Sanitary Standard for drinking water of China (1.0 mg/L), accounting for 68.1 and 91.5% of the total groundwater samples. The groundwater quality is relatively poor in this study area, and the water is unsuitable for human consumption. High-F groundwater is mainly found in the central and northern parts of the study area, and the concentrations increase in the direction of water flow. High-F groundwater is mainly found in the central and northern parts of the study area, and the concentrations increase in the direction of water flow. According to the analysis, the groundwater environment, saline water intrusion (SWI), evaporation and cation exchange are the main factors influencing the enrichment of F in the SFMZ. The neutral and weakly alkaline environment is conducive to the enrichment of F-. Cation exchange and evaporation are the most important factors in the enrichment of F. Human activity is not the main source of groundwater F. Na+ and HCO3− are adequately abundant in the groundwater environment in the study area, creating conditions that are conducive to the dissolution of fluorite and the release of F into the groundwater. An increase in the Na+ concentration and a decrease in the Ca2+ concentration can promote further dissolution of fluorite and other F-containing minerals, thereby releasing F- into the groundwater. Fluorite dissolution is prevalent in the groundwater environment, which can lead to an increase in the F concentration. This study is helpful to the development of strategies for the integrated management of high-F groundwater in coastal plains. The health risk assessment shows that long-term exposure to high-F groundwater can pose a great threat to four age clusters, especially for children and infants. The HQ values for shallow groundwater range from 0.32 to 2.89, 0.39 to 3.61, 0.56 to 5.11, and 0.42 to 3.85 for adults, teenagers, children and infants, respectively. The groundwater in this study area is not for irrigation and animal husbandry, which may indirectly affect human health.